2012
DOI: 10.1002/cncr.27641
|View full text |Cite
|
Sign up to set email alerts
|

Patient decision aids for cancer treatment

Abstract: BACKGROUND: Although patient decision aids (pDAs) are effective, widespread use of pDAs for cancer treatment has not been achieved. The objectives of this study were to perform a systematic review to identify alternate types of decision support interventions (DSIs) for cancer treatment and a meta-analysis to compare the effectiveness of these DSIs to pDAs. METHODS: The inclusion criteria for the study were: 1) all published studies using a randomized, controlled trial design, and 2) DSIs involving treatment de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…To support quality breast cancer decision-making among Chinese American women, providers need to develop decision support interventions (Spiegle et al, 2013), but these interventions must address the identified sociodemographic barriers and preferred involvement in decision-making. The breast cancer navigator (patient or nurse) and advanced practice nurses are key providers in the breast surgical oncology setting who can provide decision support and coordinate the care for ethnic minority women diagnosed with early-stage breast cancer, with the goal of high-quality breast cancer care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To support quality breast cancer decision-making among Chinese American women, providers need to develop decision support interventions (Spiegle et al, 2013), but these interventions must address the identified sociodemographic barriers and preferred involvement in decision-making. The breast cancer navigator (patient or nurse) and advanced practice nurses are key providers in the breast surgical oncology setting who can provide decision support and coordinate the care for ethnic minority women diagnosed with early-stage breast cancer, with the goal of high-quality breast cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the trials with patient decision aids or decision support interventions have resulted in higher satisfaction (Spiegle et al, 2013). However, ethnic minority and low-income women are more likely to have lower satisfaction following treatment decision-making (Lantz et al, 2005).…”
Section: Decision Outcomes In Breast Treatment: Satisfaction and Regretmentioning
confidence: 97%
See 1 more Smart Citation
“…The provision of patient centered care in oncology contexts centrally involves improving information exchange between providers and patients , one component of which is better understanding, anticipating, and tailoring care around patients’ information needs . The present study is the first to directly observe what U.S. breast cancer patients actually ask surgeons during initial consultations.…”
Section: Resultsmentioning
confidence: 94%
“…Juraskova et al 7 reported successful piloting of a decision aid to assist women considering participation in a breast cancer prevention trial. Spiegle et al 8 performed a systematic review to identify alternative types of decision support interventions (DSIs) for cancer treatment and a meta-analysis to compare the effectiveness of DSIs compared with patient decision aids. The study showed that the effectiveness of other DSIs, including question prompt list (QPLs) and audio recordings of the consultation, is similar to patient decision aids.…”
Section: Introductionmentioning
confidence: 99%